The influence of metallicity on helium and CO core masses in massive stars - Petrović Jelena (Serbian Astronomical Journal, 2023)
We present the results of 58 detailed evolutionary models of massive single stars and close binary systems with the Solar and Small Magellanic Cloud (SMC) metallicity computed with the MESA (Modules for Experiments in Stellar Astrophysics) numerical code. Helium core masses of single stars (30 M⊙ - 75 M⊙) with metallicities of 0.02 and 0.0021 are in the range of 9.26 M⊙ - 29.56 M⊙ and 11.62 M⊙ - 33.96 M⊙, respectively. Their carbon-oxygen (CO) core masses are between 5.44 M⊙ and 25.04 M⊙ vs. 8.23 M⊙ and 28.38 M⊙ for the Solar vs. SMC metallicity, accounting for an average difference of 25%. To investigate the influence of metallicity on helium and carbon-oxygen core masses in massive close Case A binary systems, detailed evolutionary models of binary systems in the mass range of 30 M⊙ to 40 M⊙ are calculated. The initial orbital period is set to 3 days and the accretion efficiency to 10%. The helium core mass range for primary stars with lower metallicity is 10.61 - 16.21 M⊙ vs. 7.94 - 11.69 M⊙ for z = 0.02. The resulting CO core masses of primary stars for the SMC metallicity are on average about 50% larger than for the Solar metallicity, so the effect is more prominent than in the case of single stars. The black hole formation limit for primary stars with the SMC metallicity is under 30 M⊙. While the least massive primary stars with Solar metallicity end up as neutron stars, all primary stars with the SMC metallicity and all secondary stars complete their evolution as black holes. The double compact objects resulting from the presented models are of two types: mixed neutron star-black hole systems (4 models) and double black holes (18 models). We also derive the relation between the final helium core mass and the carbon-oxygen core mass and show that it does not depend on metallicity. We confirm the CO/helium core mass ratio to be larger in binary systems than for single stars.